Songs of Rural Education: music, territory and territoriality - Silva, Claudio Rodrigues da [UNESP]; Moraes, Agnes Iara Domingos; Torres, Julio Cesar [UNESP]; Lima, Claudia Maria de [UNESP] (Univ Federal Tocantins, Campus Tocantinopolis, 2022)
This article problematizes with bibliography and related documents support aspects of the lyrics of the songs that are part of Cantares da Educacao do Campo collection (MST, 2006a). These songs are considered to address recurring issues in academic-scientific documents and productions related, directly or indirectly, to Rural Education. The themes presented in the lyrics of the songs in this collection are interrelated and, ultimately, imply criticism of the capitalist mode of production. Issues such as solidarity, diversity, citizenship, freedom, happiness, respect for dignity and unity among rural and city workers are addressed by the songs. The songs present society as a historical formation which is the result of human intervention. Therefore, society can and also it needs to be structurally transformed. Moreover, these songs have educational potential and integrate political strategies of rural social movements that act in defense of agrarian reform and the right to school education, in accordance with the principles of rural education, such as MST. Another fundamental question that arises is the conquest and maintenance of territory and territoriality through music.
Keywords: Rural education; Vocal music; Folklore; Social movements and education